Peningkatan Keterampilan Membaca Pemahaman Teks Narasi Menggunakan Model PQ4R di Kelas IV SDN 11 Ampang Kota Padang - Cahyatul, Azizah; Suriani, Ari; Azima, Nana Fauzana; Sukma, Elfia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the improvement of students' reading comprehension skills using the PQ4R model in grade IV of SDN 11 Ampang, Padang City. This research is a class action research consisting of four stages, namely planning, implementation, observation, and reflection. Research data were obtained from the results of planning, implementation, and observation using the PQ4R model. The data collection techniques are observation, test, and non-test. The subjects of the study were teachers and students of grade IV of SDN 11 Ampang Padang City which amounted to 15 people. The results of the study showed that: First, the teaching module of the first cycle obtained an average of 87,49% (B), increasing in the second cycle to 96.42% (SB). Second, the results of the implementation of teacher aspect learning in the first cycle were obtained on average 90.62% (B), increasing in the second cycle to 96.87% (SB). Third, the results of the implementation of learning aspects of students in the first cycle were obtained on average 79,66% (C), increasing in the second cycle to 93.75% (SB). Fourth, the results of the knowledge aspect of the first cycle students were obtained on average 80.67% (C), increasing in the second cycle to 94% (SB). Fifth, the results of reading comprehension skills in narrative texts of students in the first cycle were obtained on average 71,25% (C), increasing in the second cycle to 92.22% (SB). Thus, it can be concluded that the PQ4R model can improve the reading skills of reading and narrative text comprehension of students in grade IV of SDN 11 Ampang, Padang City.